Pancasila sebagai Dasar Pembangunan Hukum Di Indonesia - Any Ismayawati (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2017)
This paper aims to examine the urgency of Pancasila in the National Law Development Therefore, why Pancasila should be guided in every formation of law in Indonesia. How does the philosophical foundation of Pancasila use as a guide in the development of national law and what its juridical basis.Pancasila is the ideology of the Indonesian nation, is a crystallization of the noble values of the Indonesian nation derived from religious values and customary values, believed to be true, and became the basis and guidance of the behavior of the Indonesian nation in the life, nation and state. Based on that, Pancasila becomes the philosophical foundation of the development of national law because the law can be enforced and effective if the law is based on religious values, customs values and state law. In addition, the foundation of the Pancasila state is the source of all sources of law in Indonesia so that it becomes the necessity of Pancasila as the philosophical foundation in the development of law in Indonesia.the legal basis for the use of Pancasila as the foundation / guideline in the development of national law is included in Law Number 10 of 2004 on the Establishment of Legislation which is later enhanced by Law Number 12 Year 2011 on the Establishment of Laws and Regulations. In Article 2 of Law Number 12 of 2011 explicitly stated that Pancasila is the source of all sources of law. the contents of Article 2 implies that in the formation of any legislation should not conflict with the values contained in the principles of Pancasila